1992
DOI: 10.1037/1040-3590.4.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the discriminant validity of phallometric assessment data.

Abstract: Independent data sets from phallometric assessment studies were analyzed to examine methods of maximizing the discriminant validity of phallometric testing. Community volunteers and non-sexoffender patients were compared with rapists and child molesters recruited primarily from a maximum security psychiatric institution. The results indicated that the discriminant validity of phallometric assessments is enhanced by the use of (a) z (rather than raw) scores to compensate for individual differences in responsivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
156
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 55 publications
6
156
0
1
Order By: Relevance
“…In a study by Earls, Quinsey, and Castonguay (1987), z scores were found to describe the significantly highest proportion of variance (52.7%) in comparison to %FE (32.5%) and raw scores (30.1%). This was supported by Harris, Rice, Quinsey, Chaplin, and Earls (1992), who found z scores to be slightly superior to percentage of full erection. Only one study demonstrated the superiority of %FE to z score transformations as they did not distort the data as much (Barbaree & Mewhort, 1994).…”
Section: Statistical Issuesmentioning
confidence: 65%
See 2 more Smart Citations
“…In a study by Earls, Quinsey, and Castonguay (1987), z scores were found to describe the significantly highest proportion of variance (52.7%) in comparison to %FE (32.5%) and raw scores (30.1%). This was supported by Harris, Rice, Quinsey, Chaplin, and Earls (1992), who found z scores to be slightly superior to percentage of full erection. Only one study demonstrated the superiority of %FE to z score transformations as they did not distort the data as much (Barbaree & Mewhort, 1994).…”
Section: Statistical Issuesmentioning
confidence: 65%
“…Although Harris et al (1992) and Murphy and Barbaree (1994) found peak responses to produce more reliable and sensitive indices, Launay (1999) found that both methods provided acceptable outcomes. In the study by Harris et al (1992), better discrimination between offender types was obtained with indices than with scores based on individual categories. Quinsey and Chaplin (1984) found rape indices to be clearly superior in the discrimination of rapists and nonrapists.…”
Section: Statistical Issuesmentioning
confidence: 96%
See 1 more Smart Citation
“…Standardizing the responses minimizes the effect of individual variation in overall responsiveness (Harris, Rice, Quinsey, Chaplin, & Earls, 1992).…”
Section: Treatment Of Genital and Subjective Arousal Datamentioning
confidence: 99%
“…Standardizing responses minimizes the effect of individual variation in responsiveness (Harris et al, 1992). Responses to the post-stimulus questions were averaged for each category and not standardized.…”
Section: Treatment Of Genital and Subjective Arousal Datamentioning
confidence: 99%